2002
DOI: 10.3346/jkms.2002.17.5.655
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Postherpetic Neuralgia

Abstract: The investigation was aimed to determine prognostic factors related to postherpetic neuralgia (PHN), and treatment options for preventing PHN. The data showed 34 (17.0%) out of 188 patients with herpes zoster had severe pain after 4 weeks, and 22 (11.7%) after 8 weeks, compared with 109 (58.0%) at presentation. The age (≥50 yr), surface area involved (≥9%), and duration of severe pain (≥4 weeks) might be the main factors that lead to PHN. On the other hand, gender, dermatomal distribution, accompanied systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is characterized as a sharp, burning or stabbing pain which is usually associated with irreparable damage to the peripheral nervous system. [13] It can affect the quality of life of patients because of loss of productivity and the associated cost of treatment. [4] Currently, the general clinical treatment is pharmacological intervention which might lead to considerable risk of side effects especially from long-term drug use.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized as a sharp, burning or stabbing pain which is usually associated with irreparable damage to the peripheral nervous system. [13] It can affect the quality of life of patients because of loss of productivity and the associated cost of treatment. [4] Currently, the general clinical treatment is pharmacological intervention which might lead to considerable risk of side effects especially from long-term drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several serious complications of zoster (ophthalmic, splanchnic, cerebral, motor complications), the most common and most feared one in immunocompetent adults is postherpetic neuralgia (PHN). Reported incidences of PHN range between 18% and 33% depending on patient age and assessment time after the infection [16]. A recent study reported that 24% of the patients studied had postherpetic neuralgia pain for more than 90 days after rash onset.…”
Section: Introductionmentioning
confidence: 99%
“…2,11 Studies by independent groups of investigators have now established that greater acute pain severity, 12,13 greater rash severity, 14,15 and the presence of a painful prodrome preceding the rash 16,17 are additional risk factors for PHN. 2,11 Studies by independent groups of investigators have now established that greater acute pain severity, 12,13 greater rash severity, 14,15 and the presence of a painful prodrome preceding the rash 16,17 are additional risk factors for PHN.…”
mentioning
confidence: 99%